Odpowiedź :
1)
-3(x - 2) = -12 /:(-3)
x - 2 = 4
x = 4 + 2
x = 6
2)
6(2x + 1) = 3(3x - 8) /:3
2(2x + 1) = 3x - 8
4x + 2 = 3x - 8
4x - 3x = -8 - 2
x = -10
3)
4 + 2(x - 1) = 1
2(x - 1 ) = 1 - 4
2x - 2 = -3
2x = -3 + 2
2x = -1 /:2
x = -1/2
4)
3x - (10 + x) = 8
3x - 10 - x = 8
2x = 8 + 10
2x = 18 /:2
x = 9
5)
1/6 x - 7 = 5
1/6 x = 5 + 7
1/6 x = 12 /·6
x = 72
6)
4,5 - 3/5 x = 1,5
-3/5 x = 1,5 - 4,5
-3/5 x = -3 /· (-5/3)
x = 5
7)
x/2 + 4 = 10
x/2 = 10 - 4
x/2 = 6 /·2
x = 12
8)
5x - 3 + 2x = 4x + 9 - x
7x - 3 = 3x + 9
7x - 3x = 9 + 3
4x = 12 /:4
x = 3
9)
2x + 12 = 30 - 3x
2x + 3x = 30 - 12
5x = 18 /:5
x = 18/5 = 3³/₅
10)
8(2x - 1) + 3(4 - 5x) = 0
16x - 8 + 12 - 15x = 0
x + 4 = 0
x = -4
11)
1 - 4x + 5 + 2x = 7 + 2x
-2x + 6 = 7 + 2x
-2x - 2x = 7 - 6
-4x = 1 /:(-4)
x = -1/4
12)
2 + x/3 + 3 - x/6 = 1
2x/6 - x/6 + 5 = 1
x/6 = 1 - 5
x/6 = -4 /·6
x = -24